Pengaruh Penerapan Sistem Informasi Akuntansi dan Pengendalian Internal Terhadap Kualitas Laporan Keuangan pada Badan Pusat Statistik Kota Palembang - Sri Astuti Lelani Putri; Mega Silvia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the impact of the implementation of accounting information system and internal control on the quality of financial statements. This type of research is quantitative with the type od research used in primary data and secondary. Data were obtained thought questionnaire and interview. The research sample consisted of 54 respondents who were selected using total sampling. The results show that there is a signifikan influence on the quality of financial statements